The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/bjh.12768
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome in children and adolescents with relapsed Hodgkin lymphoma - results of the UK HD3 relapse treatment strategy

Abstract: SummaryThe purpose of this national retrospective study was to evaluate the outcome in children with relapsed or primary refractory Hodgkin lymphoma Other poor prognostic factors included advanced stage disease at relapse and B symptoms at first diagnosis. The most important factor associated with salvage failure was time to relapse. Survival outcome in children with primary refractory HL is poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…However, the patients in our cohort were not the most favorable. Multiple studies have shown remission duration <1 year, presence of extranodal disease, and B symptoms at relapse to be important prognostic factors in relapsed/refractory HL . Likewise, a multivariate analysis of 606 children, adolescents, and young adults with relapsed or refractory HL (median age 23 years, range 3–29 years) who underwent ASCT demonstrated similar results .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, the patients in our cohort were not the most favorable. Multiple studies have shown remission duration <1 year, presence of extranodal disease, and B symptoms at relapse to be important prognostic factors in relapsed/refractory HL . Likewise, a multivariate analysis of 606 children, adolescents, and young adults with relapsed or refractory HL (median age 23 years, range 3–29 years) who underwent ASCT demonstrated similar results .…”
Section: Discussionmentioning
confidence: 69%
“…The majority of published literatures in pediatric cohorts have employed computed tomography (CT) measurements to assess pretransplant disease status, and data on the predictive value of pretransplant FI in pediatrics are very limited. Based on the adult experience, the treatment approach at the Dana Farber/Boston Children's Cancer and Blood Disorders Center (DF/BC CBDC) has focused on getting patients with relapsed or refractory HL into complete metabolic remission before autologous transplant.…”
Section: Introductionmentioning
confidence: 99%
“…transplantation and is used either as first line or salvage treatment [1][2][3][4]. The history of allogeneic HSCT goes back to the 1980 s and indications, conditioning regimens, and donor sources have changed enormously since then [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The Swiss Pediatric Oncology Group (SPOG) M. Ansari 6,7 , M. Beck Popovic 13 , J. P. Bourquin 14 , P. Brazzola 15 , J. Greiner 16 , J. Rössler 12 , F. Schilling 17 , K. Scheinemann 2,8,9 , N. von der Weid 4…”
mentioning
confidence: 99%
“…Several studies have suggested extrapolating data on the benefit of HDC and auto-SCT from the literature on adults. 4-7 The aim of this study was to evaluate the outcomes of children and adolescents with relapsed or refractory HL treated with HDC and auto-SCT at our institution. In a resource-limited setting such as ours, outcomes were analyzed in progressive HL to decide whether to continue to offer this mode of therapy to patients.…”
Section: Introductionmentioning
confidence: 99%